Comparison of two novels: Gone with the wind by Margaret Mitchell and Anna Karenina by Lev Nikolayevich Tolstoy. - Mahliyo Saydaliyeva Ulug’bek qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Family is illuminated in the literature unlimited times. However, it never ages. In this article “Gone with wind” by Margaret Mitchell and “Anna Karenina” by Lev Tolstoy are compared. Family adoration is the main motive for these choose. Family is inevitable and unavoidable theme in the literature of all ages. Every writer can create something new or one can cover old one with new.